Let's Turn the Lights Off to Turn the Stars On - Pinto, G. A. (Open Schools Journal for Open Science, 2020)
In this project, the causes and consequences of light pollution were discussed. The students concluded that light pollution is not only responsible for the “disappearance” of the starry sky in cities, but also a threat to living beings and a huge waste of energy. They also concluded that the measures to avoid light pollution are within the reach of citizens and municipalities and are based on the use of energy-efficient exterior lighting that directs light only downwards. Students shared their findings with the community and, at the same time, developed an interest in Astronomy, together with their families.